Evaluation of Serological and Molecular Tests Used for the Identification of Toxoplasma gondii Infection in Patients Treated in an Ophthalmology Clinic of a Public Health Service in São Paulo State, Brazil - Murata, Fernando Henrique Antunes; Previato, Mariana; Frederico, Fábio Batista; Barbosa, Amanda Pires; Nakashima, Fabiana; Faria, Geraldo Magela de; Silveira Carvalho, Aparecida Perpétuo; Meira Strejevitch, Cristina da Silva; Pereira-Chioccola, Vera Lucia; Castiglioni, Lilian; de Mattos, Luiz Carlos; Siqueira, Rubens Camargo; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Ocular toxoplasmosis is one of the most common complications caused by the infection with the parasite Toxoplasma gondii. The risk of developing eye lesions and impaired vision is considered higher in Brazil than other countries. The clinical diagnosis is difficult and the use of sensitive and specific laboratorial methods can aid to the correct diagnosis of this infection. We compared serological methods ELISA and ELFA, and molecular cPCR, Nested PCR and qPCR for the diagnosis of T. gondii infection in groups of patients clinically evaluated with ocular diseases non-toxoplasma related (G1 = 185) and with lesions caused by toxoplasmosis (G2 = 164) in an Ophthalmology clinic in Brazil. Results were compared by the Kappa index, and sensitivity (S), specificity (E), positive predictive value (PPV), and negative (NPV) were calculated. Serologic methods were in agreement with ELISA more sensitive and ELFA more specific to characterize the acute and chronic infections while molecular methods were discrepant where qPCR presented higher sensitivity, however, lower specificity when compared to cPCR and Nested PCR.